THE ROLE OF ENGLISH AS A LINGUA FRANCA IN GLOBAL MARKETING - Masharipova Mohinur Mamur qizi,; Hasanova Sitora, (TADQIQOTLAR, 2026)
Abstract: In the contemporary globalized economy, English has assumed the role  of  a  lingua  franca,  functioning  as  the  primary  medium  of  communication  in international  business  and  marketing.  This  article  examines  how  English  operates within global marketing practices, focusing on its influence on brand communication, consumer  perception,  and  cross-cultural  strategy.  Drawing  on  interdisciplinary perspectives  from  sociolinguistics,  marketing  theory,  and  globalization  studies,  the paper  analyzes  both  the  advantages  and  the  limitations  of  relying  on  English  as  a dominant  communicative  tool.  The  findings  indicate  that  while  English  enhances efficiency, standardization, and global brand identity, its uncritical use may lead to cultural  misalignment  and  reduced  local  engagement.  The  study  concludes  that effective global marketing requires a balanced approach that integrates English with localized linguistic and cultural adaptation.